Phylogeny and speciation in Saxifraga sect. Ciliatae (Saxifragaceae): Evidence from psbA‐trnH, trnL‐F and ITS sequences. Issue 4 (1st August 2015) - Gao, Qing-Bo; Li, Yin-Hu; Gornall, Richard J.; Zhang, Zhuo-Xin; Zhang, Fa-Qi; Xing, Rui; Fu, Peng-Cheng; Wang, Jiu-Li; Liu, Hai-Rui; Tian, Zun-Zhe; Chen, Shi-Long
Abstract: Nearly half of the species in the large genus Saxifraga belong to Saxifraga sect. Ciliatae, a largely Sino‐Himalayan taxon. We report here that evidence from chloroplast DNA sequences (psbA‐trnH, trnL‐F) and from nuclear sequences (ITS) indicates that this section is monophyletic and composed of at least three main lineages, corresponding to (1) a clade made up of species from S. subsect. Gemmiparae, subsect. Cinerascentes, subsect. Flagellares and subsect. Hemisphaericae, in which the last three subsections are nested in the first; (2) a clade of species belonging to S. subsect. Rosulares (including S. subsect. Serpyllifoliae); and (3) a clade of species belonging to S. subsect. Hirculoideae. Species relationships in S. subsect. Rosulares and subsect. Hirculoideae are not well resolved. A molecular clock analysis indicates that the diversification of S. sect. Ciliatae into its three lineages dates from ca. 9.48 Ma, coinciding with orogenic events associated with one of the most important phases of uplift of the Qinghai‐Tibet Plateau. Extensive diversifications within S. subsect. Rosulares and subsect. Hirculoideae have been more recent (ca. 4.51 Ma and 2.12 Ma, respectively), again correlated with Qinghai‐Tibet Plateau uplift events and, in the case of S. subsect. Hirculoideae, have occurred at a rate comparable to that seen in the radiation of Hawaiian fruit flies.